THE FUTURE OF GENERATIVE AI IN EDUCATION: OPPORTUNITIES FOR ENHANCING TEACHING AND LEARNING - Akbar Syaiful Luneto; Kim Minho; Nurul Inayah Bachmid (Al-Hijr: Journal of Adulearn World, 2026)
Rapid advancements in Generative Artificial Intelligence (Generative AI) have transformed educational practice by enabling intelligent content generation, personalized learning support, adaptive tutoring, automated feedback, and innovative instructional design. Expanding adoption of these technologies has created substantial opportunities for improving teaching and learning while simultaneously raising concerns regarding academic integrity, ethical governance, information reliability, and the evolving role of educators. This study aimed to examine the future potential of Generative AI for enhancing educational processes by investigating its pedagogical opportunities, instructional effectiveness, and broader implications for teaching and learning. A mixed-methods sequential explanatory design was employed, integrating quantitative evidence from learning analytics, academic performance, and standardized educational measures with qualitative data collected through interviews, classroom observations, reflective journals, and institutional document analysis. Findings demonstrated that Generative AI significantly improved academic achievement, learner engagement, creativity, critical thinking, self-regulated learning, instructional effectiveness, and course completion when implemented within well-structured pedagogical environments supported by active educator facilitation. Qualitative evidence further indicated that responsible integration depended on human oversight, ethical guidance, transparent institutional policies, and the development of learners' critical digital literacy. Results suggest that Generative AI functions most effectively as a collaborative pedagogical partner rather than a substitute for educators. Human-centered implementation supported by responsible governance provides a sustainable pathway for educational innovation and future digital transformation across diverse learning environments.